ANALYSIS AND INTERPRETATION OF WEAR IN POLYMER MATERIALS BASED ON TRIBOLOGICAL INVESTIGATIONS - Marchuk, Roman; Mnatsakanov, Rudolf (Problems of Friction and Wear, 2023)
The analyzed properties of polymer materials related to wear resistance and vibration absorption capabilities, utilized in the production of sliding pairs, have been explored. The perspective of employing polymer-metal friction pairs in industrial machinery, pharmaceuticals, and the food industry has been substantiated. To effectively control any mechanical system with sliding motion under optimal parameters, indicating tribological characteristics for materials in frictional contact is a convenient means for swiftly characterizing tribological behavior when operating conditions are variable. Through experimental investigation, factors influencing the wear of polymer specimens in contact with metal have been analyzed. The materials subjected to tribological analysis are polymer materials such as Sustamid 66 gray, Sustapei, and SusTamid 6G OL, manufactured by the Röchling Group, in contact with steel 30KhGSA. All selected polymer materials are designed for use in pairs with sliding contact.